The benefits of using confocal laser endomicroscopy in the diagnosis of gastric cancer and precancerous lesions: a case report - Peng, Xiaoting; Zheng, Ya-Ping; Zhang, Yan (Frontiers in Oncology, 2025)
BackgroundCases of early gastrointestinal cancers (EGC) are often identified as advanced stages due to the lack of typical clinical manifestations, leading to missed or delayed diagnoses. Confocal laser endomicroscopy (CLE), a novel microscopic imaging technique, enables real-time in vivo histological examination during endoscopy, providing a valuable tool for the early detection of EGC.InterventionA 62-year-old woman with a gastric antral lesion, considered a polyp or early cancer, underwent CLE during gastroscopy to refine and confirm the diagnosis.FindingsCLE imaging showed mild irregularities in the glandular architecture, thickening of the mucosal margins, the presence of pleated structures, dilated glandular openings, increased vascularity, and mild fluorescein leakage, all consistent with mild to moderate inflammatory changes. No features suggestive of malignant lesions were revealed.ConclusionCLE may play a pivotal role in the early differentiation of benign and malignant gastrointestinal lesions. While not yet a replacement for histopathology, CLE demonstrates significant clinical utility and potential for improving the accuracy of early cancer detection and long-term monitoring.